PERAN PUBLIC RELATION DALAM PELAKSANAAN PROGRAM COORPORATE SOCIAL RESPONSIBILITY PADA PT. TELKOMSEL AMBON - RIDO DOMINGGUS LATUHERU (JURNAL BADATI, 2021)
As PT Telkomsel's CSR Program also has the main commitments, namely: helping the community and providing optimal contributions to the community based on the 5 main pillars that are its CSR mission, namely: (1) building human capital; (2) Maintain social cohesion; (3) Strengthen economic value; (4) Encourage good government; and (5) Protecting the Environment.This is certainly inseparable from the intervention of the Public Relations (PR) department or other departments that carry out PR functions. At PT Telkomsel, PR is under the auspices of the Personnel department. PT Telkomsel Maluku can still "live" in harmony with stakeholders so far and it is almost said that there is no "skewed" news from other communities due to the implementation of CSR. This is the interest of researchers to analyze the function of PR in implementing one of the programs, namely the CSR program in Ambon. The formulation of the problem in this research is How the Role and Public Relations of PT. Telkomsel in implementing the CSR Program? The Research Method in this paper is Qualitative Descriptive